2002
DOI: 10.1074/jbc.m109176200
|View full text |Cite
|
Sign up to set email alerts
|

Rap-specific GTPase Activating Protein follows an Alternative Mechanism

Abstract: Rap1 is a small GTPase that is involved in signal transduction cascades. It is highly homologous to Ras but it is down-regulated by its own set of GTPase activating proteins (GAPs). To investigate the mechanism of the GTPhydrolysis reaction catalyzed by Rap1GAP, a catalytically active fragment was expressed in Escherichia coli and characterized by kinetic and mutagenesis studies. The GTPase reaction of Rap1 is stimulated 10 5 -fold by Rap1GAP and has a k cat of 6 s ؊1 at 25°C. The catalytic effect of GAPs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 68 publications
3
67
1
Order By: Relevance
“…3A). These 2 PKA phosphorylation sites on Rap1GAP are located in an area of unknown significance C-terminal to a well-characterized GAP domain (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). These 2 PKA phosphorylation sites on Rap1GAP are located in an area of unknown significance C-terminal to a well-characterized GAP domain (11).…”
Section: Resultsmentioning
confidence: 99%
“…4). To compensate for the increase in Rap1GAP activity that accompanies Rap1GAP overexpression, we coexpressed Rap1 with a Gly12Val mutation that greatly increases the affinity of Rap1 for GTP while remaining susceptible to hydrolysis and inactivation by GAPs (11)(12)(13). Using a RalGDS pull-down assay to measure Rap1 activity (14), we found that mutation of Ser-441 and Ser-499 to alanine resulted in a lower level of active Rap1.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike other GAPs, Rap1GAP1 uses a catalytic asparagine to stimulate GTP hydrolysis, which targets interactions with Rap and limits its interactions with other small G proteins (5). While the main function of Rap1Gap1 is thought to be the down-regulation of Rap activity by GTP hydrolysis, it is possible that other functions exist.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Rap1GAP has been shown to utilize a unique catalytic asparagine to stimulate GTP hydrolysis, which provides specificity for Rap (14). In addition, the presence of two lysines within the catalytic region of Rap1 and not present in Ras, Rho, and Rab (14) further ensures the specificity of the catalytic asparagine in Rap1 to function in GTP hydrolysis (5,14). In peripheral T cells expressing transgenic Rap1GAP1, the activation of Rap1 by soluble anti-CD3 cross-linking was significantly reduced (Fig.…”
Section: Ctla-4 Inhibits Erks and Activates Rap1mentioning
confidence: 99%
“…However, once priming or tolerance is established, it is possible that rewiring of Rap1 signaling occurs, reflecting differential levels/kinetics of Rap1 expression. Consistent with a role for signal strength in directing these processes, Boussiotis and associates (48) suggested that the differential responses of the Rap1V12-and Rap1E63-Tg mice might reflect the finding that the Rap1E63 mutant exhibits five times the biological activity of Rap1V12 (61) being insensitive to the negative regulator of Rap1, Rap1GAP (62). This proposal is supported by recent studies showing that mice that are deficient in the Rap1GAP, SPA-1, exhibit defective ERK activation and progressive unresponsiveness or tolerance of T cells (63).…”
Section: Discussionmentioning
confidence: 83%